Home-based screening tools for amblyopia: a systematic review protocol - Chung Shen Chean; Samantha Sii; Mervyn G Thomas; Helen J Kuht; Sohaib R Rufai (BMJ Open)
Introduction Amblyopia is an important public health concern associated with functional vision loss and detrimental impact on the physical and mental well-being of children. The gold standard for diagnosis of amblyogenic conditions currently involves screening by orthoptists and/or ophthalmologists. The bloom of technology enables the use of home-based screening tools to detect these conditions at an early stage by the layperson in community, which could reduce the burden of screening in the community, especially during restrictions associated with the COVID-19 pandemic. Here, we propose a systematic review aiming to evaluate the accuracy and reliability of home-based screening tools compared with the existing gold standard.Methods and analysis We aim to search for studies involving home-based screening tools for amblyopia among children aged under 18 years. Oxford Centre for Evidence-Based Medicine Level 4 evidence and above will be included, without language or time restrictions. The following platforms will be searched from inception to 31 August 2021: PubMed, Medline, The Cochrane Library, Embase, Web of Science Core Collection and Clinicaltrials.gov. Two independent reviewers will identify studies for inclusion based on a screening questionnaire. The search and screening will start on 14 August 2021 until 1 October 2021. We aim to complete our data analysis by 30 November 2021. Risk of bias will be assessed using the Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) tool for diagnostic accuracy studies only. Our primary outcome measure is the diagnostic accuracy of home-based screening tools, while secondary outcome measures include validity, feasibility, reproducibility and cost-effectiveness, where available.Ethics and dissemination Ethical approval is not necessary as no primary data will be collected. The findings will be disseminated through presentations at scientific meetings and peer-reviewed journal publication.PROSPERO registration number CRD42021233511.